Spectroscopic markers for uranium(vi) phosphates. Part II: the use of time-resolved photoluminescence. Issue 2 (4th January 2017) - Massuyeau, F.; Perry, D. L.; Kalashnyk, N.; Faulques, E.
Abstract : 3D time-resolved luminescence imaging by means of a streak camera can detect and discriminate low amounts of various uranyl minerals via concomitant analysis of spectral properties and photoluminescence lifetimes. Abstract : Detection of uranium hydrates that are relevant for environmental sustainability and adsorption at surfaces is effected using time-resolved photoluminescence spectroscopy (TRPL) with simultaneous lifetime and spectral acquisitions. The study is the second paper devoted to this topic (part I: Faulques et al. RSC Adv., 2015, 5, 71219) and focuses on photoluminescence (PL) phenomena. When a temporal dimension is added, the TRPL technique surpasses, via PL decay analysis, steady-state approaches for discriminating minerals with very similar optical and PL spectra. Further, estimates of quantum yields and nonradiative lifetimes can be given. The results are pertinent in the context of remote sensing of parent hazardous uranyl compounds in the environment.